The Animistic Way: Contemporary Paganism and the Posthuman - Dos Santos, Victoria (Poligrafi, 2021)
This article aims to explore the affinities between contemporary Paganism and the posthuman project in how they approach the non-human natural world. On the one hand, posthumanism explores new ways of considering the notion of humans and how they are linked with the non-human world. On the other hand, Neopaganism expands this reflection to the spiritual domain through its animistic relational sensibility. Both perspectives challenge the modern paradigm where nature and humans are opposed and mutually disconnected. They instead propose a relational ontology that welcomes the “different other.” This integrated relationship between humans and the “other than human” can be understood through the semiotic Chora, a notion belonging to Julia Kristeva that addresses how the subject is not symbolically separated from the world in which it is contained.